2007
DOI: 10.1086/521226
|View full text |Cite
|
Sign up to set email alerts
|

The Variant inv(2)(p11.2q13) Is a Genuinely Recurrent Rearrangement but Displays Some Breakpoint Heterogeneity

Abstract: Human chromosome 2 contains large blocks of segmental duplications (SDs), both within and between proximal 2p and proximal 2q, and these may contribute to the frequency of the common variant inversion inv(2)(p11.2q13). Despite their being cytogenetically homogeneous, we have identified four different breakpoint combinations by fluorescence in situ hybridization mapping of 40 cases of inv(2)(p11.2q13) of European origin. For the vast majority of inversions (35/40), the breakpoints fell within the same spanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…We recently studied two of these common variant inversions, namely inv(2)(p11q13) and inv(10)(p11.2q21.2). We showed for the chromosome 2 inversion that, as expected, the inversion had occurred on numerous occasions on diVerent haplotypic backgrounds and that the breakpoints occurred in regions of high sequence homology [segmental duplications (SDs)] presumably accounting for the repeated occurrence of this inversion (Fickelscher et al 2007). However, the "variant" inv(10)(p11.2q21.2) was unexpectedly found to be IBD in all 20 apparently unrelated families studied from Wve diVerent countries, suggesting that this inversion has a single ancestral founder among Northern Europeans (Gilling et al 2006).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…We recently studied two of these common variant inversions, namely inv(2)(p11q13) and inv(10)(p11.2q21.2). We showed for the chromosome 2 inversion that, as expected, the inversion had occurred on numerous occasions on diVerent haplotypic backgrounds and that the breakpoints occurred in regions of high sequence homology [segmental duplications (SDs)] presumably accounting for the repeated occurrence of this inversion (Fickelscher et al 2007). However, the "variant" inv(10)(p11.2q21.2) was unexpectedly found to be IBD in all 20 apparently unrelated families studied from Wve diVerent countries, suggesting that this inversion has a single ancestral founder among Northern Europeans (Gilling et al 2006).…”
Section: Introductionsupporting
confidence: 64%
“…Thus there are three diVerent molecular breakpoint combinations for inversions designated as inv(14)(q24q32). Similarly, FISH mapping previously identiWed four diVerent breakpoint combinations among cytogenetically (Fickelscher et al 2007). Unsurprisingly, given that breakpoints deWned cytogenetically could span several Mb, by chance some inversions which appear to be recurrent will in fact have distinct breakpoints at a higher level of resolution.…”
Section: Discussionmentioning
confidence: 92%
“…For polymorphic inversions found in natural populations, the recurrence of inversions mediated by NAHR between SDs had already been postulated by comparison of different lineages in mammals [59] or primates [21], [67], and there was some evidence that it could occur in humans as well [12], [68]. In addition, experimentally it was suggested that some inversions could appear repeatedly in human cells [69], [70], although these results should be confirmed with independent techniques.…”
Section: Discussionmentioning
confidence: 97%
“…One group of investigators, however, has reported an increased risk for miscarriage among carriers of a pericentric inversion of chromosome 2 [inv(2)(p11q13), Fig. 9.9 ] [ 85 ] . Other inversions have been observed in many families but are not without consequence.…”
Section: Pericentric Inversionsmentioning
confidence: 99%